Integrated water resources management: A new strategy for DSS development and implementation. Issue 2 (10th November 2022) - Ma, Qiang; Gourbesville, Philippe
Abstract: Although the recent concept of Integrated Water Resources Management (IWRM) is continuously searching for modern operational approaches to be implemented in practice, the Decision Support Systems (DSSs) have been considered a major effective tool for supporting IWRM. According to the weaknesses and limitations in the current DSSs, this paper presents a new DSS development strategy based on an architecture design including higher levels of competitive advantages in system flexibility, product maintenance, and user acceptance. Instead of producing a DSS as a stand‐alone product limited to real‐time monitoring, the selected approach presents a design for a real‐time DSS service setup with a multilayered user interface and a multimodular modeling system. The methodology has been used and implemented over the Var catchment (2800 km 2 ) and has been validated with an operational application. The designed DSS is currently used by the local management authorities with a high level of user satisfaction with monitoring and forecast services. The obtained result underlines the promising applicability of the proposed approach for other DSSs addressing utilities.